The criteria of anagogical methods in Tafsīr al-Alusi - Sulaiman, Kabuye Uthman; Ismail, Nur Insyrah (2018)
This research is to review the methodology used by Alūsī in his Tafsir (Allegorical Interpretation) according to his interpretation in analysing the evidence from the Qur’ān and Sunnah, highlighting the role of the curriculum and its provisions in relation to the allegorical interpretation. Based on the interpretations, the best approach would be to understand the Qur’ān and Sunnah as it would protect the authenticity. It has been shown from research that any misinterpretation of the Qur’ān and Sunnah will lead to differences of opinions thus influencing the mindsets of society. Henceforth it affects the socio-political and economic interpretation of Islam. This research adopts the methodology of induction, the comparison of opinions and in depth analysis of the subject matter. The conclusion is derived from all of the above factors coupled with the researchers’ own analysis and opinions.